RECONCEPTION OF REGULATION OF THE MINISTER OF MANPOWER CONCERNING DOMESTIC APPRENTICESHIP TOWARDS THE FULFILLMENT OF THE RIGHT TO POCKET MONEY FOR APPRENTICES - Nasywa Nagia Anaqa (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
Regulation of the Minister of Manpower Number 6 of 2020 concerning the Implementation of Apprenticeships in the Country specifically regulates the provisions in the implementation of apprenticeships, including the rights and obligations of apprenticeship organisers and apprentices. However, in its realisation, Regulation of the Minister of Manpower Number 6 of 2020 has not regulated the standardisation of pocket money in apprenticeship agreements and details of alternative replacement pocket money provided by apprenticeship organisers if they do not provide pocket money in the form of nominal capital. This study aims to provide consideration for the government regarding the welfare of apprentices on the right to pocket money. This research uses normative legal methods and a literature data search. The reconception of Regulation of the Minister of Manpower Number 6 of 2020 needs to be taken into consideration by the government through related agency regulations or higher regulations to provide minimum standardisation of pocket money in internship agreements, as well as budget formation through the Ministry of Finance Input Cost Standard, which determines the government budget to provide an honorarium for apprentices from state agencies or educational institutions.